Symptoms of Mental Health during Covid-19 Survivors: A Cross-Sectional Study in Indonesia - Pharmasinta Putri Hapsari; Fatimatuz Zahra Oviary Satryo; Lily Aina; Nanda Ardianto; Melinda Putri Amelia Rachman; Fauzul Meiliani; Eunice Marlene Sicilia Kundiman (WMJ (Warmadewa Medical Journal), 2022)
Abstract The Covid-19 pandemic can influence the mental condition of patients and affect their immunity levels. This article aims to investigate the mental health symptoms and disorders of Covid-19 survivors. This was observational and cross-sectional research. A total of 175 respondents participated, 84% of them being women and 16% being men. Their work history includes health workers at 75.4% and others at 24.6%. Respondents who have experienced anxiety are 32%, sadness was 25.7%, fear was 22.9%, and panic was 14.3%. The logistic regression showed that all of the tested characteristics have no significant effect on the respondents’ mental states of anxiety, fear, and panic, with p-values ​​of 0.388, 0.893, and 0.166; 0.245, 0.691, and 0.353; 0.612, 0.410, and 0.828. However, from the test results, it was observed that gender has a significant effect on sadness with a p-value of 0.027 and OR value of 5.308 (CI = 1.204-23.399). The percentage of women respondents that experienced sadness was 29.3% and men respondents were 7.1%. Other characteristics, which are age and work history, have no significant effect on sadness, with p-values ​​of 0.650 and 0.844 respectively. There are no variables that affect anxiety, fear, and panic. Feelings of sadness in patients are influenced by gender. Keywords: anxiety; Covid-19; mental disorder; mental health